Succeeding in college with Asperger syndrome : a student guide - Harpur, John, 1958- (Jessica Kingsley, 2004)
College life is particularly stressful for students with Asperger Syndrome (AS) and the resources that colleges provide for such students are often inadequate. This much needed guide provides information to help these students prepare successfully for the rites and rituals of studying, interact with staff and fellow students, cope with expectations and pressures, and understand their academic and domestic responsibilities. How will I cope with the workload? What do I do if I feel ill? How do I make friends and initiate relationships with the opposite sex? Drawing on first hand interviews with.